Embodying the Self: Neurophysiological Perspectives on the Psychopathology of Anomalous Bodily Experiences - Andrea Raballo (Frontiers Research Topics, 2018)
Since the beginning of the 20th Century, phenomenology has developed a distinction between lived body (Leib) and physical body (Koerper), a distinction well known as body-subject vs. body-object (Hanna and Thompson 2007). The lived body is the body experienced from within - my own direct experience of my body lived in the first-person perspective, myself as a spatiotemporal embodied agent in the world. The physical body on the other hand, is the body thematically investigated from a third person perspective by natural sciences as anatomy and physiology. An active topic affecting the understanding of several psychopathological disorders is the relatively unknown dynamic existing between aspects related to the body-object (that comprises the neurobiological substrate of the disease) and the body-subject (the experiences reported by patients) (Nelson and Sass 2017). A clue testifying the need to better explore this dynamic in the psychopathological context is the marked gap that still exists between patients' clinical reports (generally entailing disturbing experiences) and etiopathogenetic theories and therapeutic practices, that are mainly postulated at a bodily/brain level of description and analysis. The phenomenological exploration typically targets descriptions of persons' lived experience. For instance, patients suffering from schizophrenia may describe their thoughts as alien (''thoughts are intruding into my head'') and the world surrounding them as fragmented (''the world is a series of snapshots'') (Stanghellini et al., 2015). The result is a rich and detailed collection of the patients' qualitative self-descriptions (Stanghellini and Rossi, 2014), that reveal fundamental changes in the structure of experiencing and can be captured by using specific assessment tools (Parnas et al. 2005; Sass et al. 2017; Stanghellini et al., 2014). The practice of considering the objective and the subjective levels of analysis as separated in the research studies design has many unintended consequences. Primarily, it has the effect of limiting actionable neuroscientific progress within clinical practice. This holds true both in terms of availability of evidence-based treatments for the disorders, as well as for early diagnosis purposes. In response to this need, this collection of articles aims to promote an interdisciplinary endeavor to better connect the bodily, objective level of analysis with its experiential corollary. This is accomplished by focusing on the convergence between (neuro) physiological evidence and the phenomenological manifestations of anomalous bodily experiences present in different disorders.